話し手の気持ちを伝える日本語表現について - Kyoji Honda (IZUMI, 2013)
ABSTRACT In this paper, we discuss how people are conveying their feelings to each other in their daily communication.In Section 2, we see certain instances where people can convey their feelings without words.In Section 3, we discuss that people convey their feelings directly and explicitly, using lexical words, and also at the same time, they utilize extra-linguistic elements, such as facial expressions, eyes, gestures, body movements, vocal tones, intonation and so on.Moreover, there are many expressions in Japanese that signal the speaker’s feelings, not by single lexical words but by some combinations of expressions.We pick up some of those expressions, and discuss what feelings they convey. Key words: feelings, silent communication, extra-linguistic, Japanese